Protection of financial consumer in consumer credit industry: The role of Central Bank of Malaysia under the Financial Services Act 2013 - Ilias, Ibtisam @ Ilyana; Hassan, Rusni; Kassim, Salina; Abu Bakar, Elistina (2017)
This paper explores the role of the central bank of Malaysia or Bank Negara Malaysia (BNM) in protecting the interest of financial consumer in consumer credit industry. Regulatory functions and enforcement powers conferred by the Financial Services Act 2013 (FSA) have been scrutinised. Despite extensive power, the paper discovers some weaknesses on sole reliance to BNM to enforce the FSA and the associated regulatory instruments. This study recommends for the establishment of a single consumer credit law regulated to be governed by a single regulator; an approach adopted by Australia which is acknowledged as having a strong consumer protection regime.